Rancang Bangun Aplikasi Midesk Berbasis Website Menggunakan Metode User Centered Design - Yehezkiel Nicholas Adanson; Gita Fadila Fitriana (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Assurance is a non-bank financial institution that carries out an agreement between the insurer and the insured to provide protection or protection suffered by the insured for financial losses arising from unexpected and uncertain events. Insurance consumers come from various circles, insurance has an agent who plays a role in marketing insurance products owned by the company. The problem with insurance users is that they often have difficulty reporting problems. Reporting problems at the Manulife insurance company still cannot help optimally, as evidenced by the use of Notepad and Microsoft Excel. Based on these problems, this research creates an application called MiDesk to help the problems faced by consumers. This application uses the user-centered UCD method so that all these processes produce products that meet user needs. The result achieved using the UCD method is a Web-based Helpdesk application. The result of this research is a web-based MiDesk application that can be used by the Manulife Helpdesk IT agent team.